Expression and prognostic value of circulating angiogenic cytokines in pancreatic cancer - Rahbari, Nuh Nabi; Schmidt, Thomas; Falk, Christine S.; Hinz, Ulf; Herber, Magdalene; Bork, Ulrich; Büchler, Markus W.; Weitz, Jürgen; Koch, Moritz (BMC cancer, 2011)
Background: The utility of circulating angiogenic cytokines (CAC) as biomarkers in pancreatic cancer has not been clarified yet. We investigated the expression and prognostic associations of seven CAC in patients with pancreatic cancer. Methods: Serum samples were collected preoperatively in patients undergoing surgery for localized pancreatic cancer (n = 74), metastatic pancreatic cancer (n = 24) or chronic pancreatitis (n = 20) and in healthy controls (n = 48). Quantitative enzyme-linked immunosorbent assays and multiplex protein arrays were used to determine circulating levels of VEGF, VEGFR-1, PlGF, PDGF-AA, PDGF-BB, Ang-1 and EGF. Multivariate analyses on cancer-specific survival were performed with a Cox proportional hazards model. Results: VEGF (p < 0.0001), PDGF-AA (p < 0.0001), Ang-1 (p = 0.002) and EGF (p < 0.0001) were differentially expressed in patients with pancreatic cancer compared to healthy controls. The presence of lymph node metastases was associated with increased levels of all CAC except for PlGF, whereas there were only minor associations of CAC with other clinicopathologic variables. The multivariate model including the entire angiogenic panel revealed high levels of circulating PDGF-AA (hazard ratio 4.58; 95% confidence interval 1.43 - 14.69) as predictor of poor cancer-specific survival, whereas high levels of PDGF-BB (0.15; 0.15 - 0.88), Ang-1 (0.30; 0.10 - 0.93) and VEGF (0.24; 0.09 - 0.57) were associated with a favorable prognosis. Conclusion: Circulating levels of certain angiogenic cytokines correlate with patients' prognosis after resection for pancreatic cancer, if a panel of several CAC is considered simultaneously. These data should be considered in future studies evaluating angiogenic factors as prognostic biomarkers and therapeutic targets in patients with pancreatic cancer.